Evaluation of the Impact of Primary Care Service Implementation on Service Quality - Feyske Youke Lumuru; Herlina Jusuf; Jusna Ahmad (Indonesian Journal of Global Health Research, 2026)
Patient satisfaction is a critical indicator in assessing the quality of healthcare services, as it influences patient loyalty and the sustainability of service utilization. This study aimed to evaluate the impact of the implementation of Integrated Primary Care (ILP) on the quality of healthcare services at Pilolodaa Primary Health Center. This study employed a qualitative research design with a case study approach. This qualitative study included nine purposively selected informants. Data were obtained through in-depth interviews and analyzed using thematic analysis with triangulation. Data were collected through in-depth interviews, direct observation, and document review. The data were then analyzed thematically using the Input–Process–Output–Impact (IPO-D) evaluation. The findings indicate that the implementation of ILP had a positive impact on service quality, as evidenced by improved cross-program coordination, enhanced service workflows, increased ease of access to healthcare services, and higher levels of patient satisfaction. However, several challenges remained, including limitations in human resources, increased digital administrative workload, and disparities in infrastructure and facilities. The implementation of ILP contributes positively to improving healthcare service quality and patient satisfaction at the primary care level. Nevertheless, addressing human resource constraints, administrative burdens, and infrastructural inequalities is essential to ensure the sustainability and optimal effectiveness of ILP implementation.